Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s12893-020-00745-4
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine green fluorescence imaging to assess bowel perfusion during totally laparoscopic surgery for colon cancer

Abstract: Background: To retrospectively evaluate the feasibility and safety of intraoperative assessment of bowel perfusion in totally laparoscopic surgery for colon cancer using indocyanine green fluorescence imaging (IGFI). Methods: From October 2017 to June 2019, consecutive patients with colon cancer who underwent totally laparoscopic surgery were enrolled retrospectively and grouped into the IGFI group (n = 84) and control group (n = 105). In the IGFI group, indocyanine green (ICG) was injected intravenously, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 29 publications
0
13
0
2
Order By: Relevance
“…A total of 1936 references were finally confirmed by the electronic search, and 73 potentially relevant studies were selected after screening the titles and abstracts. Among the 73 potentially relevant studies, a total of 32 met the inclusion criteria [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Table 1 and Table S1 summarize the study characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 1936 references were finally confirmed by the electronic search, and 73 potentially relevant studies were selected after screening the titles and abstracts. Among the 73 potentially relevant studies, a total of 32 met the inclusion criteria [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Table 1 and Table S1 summarize the study characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…The readmission rate in a 30-day follow-up was 4.6% vs. 7.2%, respectively, in the ICG vs. the non-ICG group (RR = 0.91; 95% CI: 0.48–1.70; I 2 = 14%; p = 0.76) [ 23 , 37 , 43 ]. However, the readmission rate in a 60-day follow-up equaled 15.5% vs. 10.6% (RR = 0.85; 95% CI: 0.16–4.42; I 2 = 61%; p = 0.85) [ 28 , 33 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ICG is a safe dye, and its adverse reactions are rarely reported ( 50 , 51 ). In a study of 1,226 participants, adverse events were observed in only eight subjects after intravenous ICG administration of 1 to 5 mg/kg, with only one severe adverse event and no deaths reported ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the methods that allow intraoperative visualization of microcirculation, the most common one is fluorescence imaging with the indocyanine green as a fluorophore [12][13][14]. Tissue perfusion can be assessed using laser Doppler flowmetry [15,16], laser speckle contrast imaging (LSCI) [17,18], sidestream dark field (SDF) microscopy [19,20], incident dark field (IDF) microscopy [21], and hyperspectral imaging (HSI) [22].…”
Section: Introductionmentioning
confidence: 99%